Diversity and Abundance of Mangrove Gastropods in Setiu Wetlands and Matang Mangrove Forest Reserve, Peninsular Malaysia - Baharuddin, Nursalwa; Satyanarayana, Behara (ILMU KELAUTAN: Indonesian Journal of Marine Sciences, 2024)
Mangrove gastropods, a highly diverse group of mollusks, play a critical yet often overlooked role in mangrove ecosystems. This study investigates the distribution and abundance of mangrove gastropods in two study sites with distinct management regimes: Matang Mangrove Forest Reserve (MMFR) and Setiu Wetlands (SW) in Peninsular Malaysia. Gastropod sampling was conducted over two days in April 2023, with one-hour visual encounter surveys performed at each study site per day. A total of 3,717 individuals, representing 26 species, were collected across both study sites. The family Ellobiidae was predominant in MMFR, while the family Littorinidae dominated in SW. Despite the higher biodiversity of both mud-dwelling and tree-dwelling species observed in MMFR, the overall low abundance of gastropods indicates negative impacts from greenwood exploitation and the widespread monoculture of Rhizophora spp. In contrast, the reduced diversity of mud-dwelling species in SW may be attributed to suboptimal sediment conditions caused by a shifted Setiu River mouth, low freshwater discharge, and increased sedimentation. This study provides precise assessments of species distribution across various microhabitats, offering essential baseline data for future ecological monitoring. Improved management practices, including habitat restoration, protection of biodiversity hotspots, and community engagement, are critical for sustaining gastropod populations and ensuring the long-term health and resilience of these vital coastal ecosystems. The findings highlight the sensitivity of gastropods to environmental changes and emphasize the need for adaptive conservation strategies to mitigate human impacts on mangrove ecosystems. This study serves as a foundation for developing effective conservation strategies to protect mangrove ecosystems, crucial for maintaining gastropod populations and the overall health of coastal ecosystems.